Challenges to women’s economic empowerment in Rural Tajikistan a study from road projects - Idei, Rika; Taniguchi, Kiyoshi; Bakhtibekova, Zulfiya (ADB Briefs)
This brief analyzes ways to economically empower women in rural Tajikistan and highlights how better integrating measures into the development of critical transport infrastructure projects can help narrow the substantial gender gap.